The influence of drill point geometry on tool life - Botak, Zlatko (Array, 2018)
Drilling is a cutting process that uses a rotary cutting tool to cut a cylindrical hole in a solid material. During machining, drill bits are exposed to rapid wear at high temperature. Sometimes, due to an ecological need for dry technology without any lubricant, the use of drill bits with coatings is required, typically titanium nitride (TiN), titanium carbon nitride (TiCN) or titanium aluminium nitride (TiAlN). This paper presents research on drilling done to determine how drill point geometry affects the drill lifetime and finished surface quality. We compared the chip removal ability and surface quality of bored holes in Hardox 500 created with high-speed steel drill bits and drill bits manufactured from hard metals, with and without coatings, under constant processing parameters. A cost/efficiency comparison was also carried out with respect to drill bit fabrication, sharpening, and use. Based on the data obtained on the damage drill points, the most economical drill bit for processing holes was determined.